2019
DOI: 10.1002/bdr2.1487
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol and cannabinoid exposure during the brain growth spurt on behavioral development in rats

Abstract: Cannabis is the most commonly used illicit drug among pregnant women. Moreover, over half of pregnant women who are consuming cannabis are also consuming alcohol; however, the consequences of combined prenatal alcohol and cannabis exposure on fetal development are not well understood. The current study examined behavioral development following exposure to ethanol (EtOH) and/or CP-55,940 (CP), a cannabinoid receptor agonist. From postnatal days (PD) 4-9, a period of brain development equivalent to the third tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 111 publications
(135 reference statements)
2
21
3
Order By: Relevance
“…Thus, the augmentation in locomotion could be the result of a decreased habituation to a novel environment compared to the CTRL group. Since habituation per se represents a learning process of the environmental setting, one could speculate that the hyper-locomotor effect observed in this study may underlie a delay in simple learning (Breit et al, 2019) rather than a prominent effect on emotionality. Further investigation of spatial learning abilities (Cannizzaro et al, 2007) of PCE progeny will clarify this point.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the augmentation in locomotion could be the result of a decreased habituation to a novel environment compared to the CTRL group. Since habituation per se represents a learning process of the environmental setting, one could speculate that the hyper-locomotor effect observed in this study may underlie a delay in simple learning (Breit et al, 2019) rather than a prominent effect on emotionality. Further investigation of spatial learning abilities (Cannizzaro et al, 2007) of PCE progeny will clarify this point.…”
Section: Discussionmentioning
confidence: 90%
“…Previous findings from our group demonstrated that perinatal exposure to THC (GD 15 to PND 9) altered social play and induced anxiety‐like behaviours in the male rat offspring (Trezza et al, ). Moreover, it has been recently shown that the postnatal exposure to the cannabinoid receptor agonist CP 55,940 from PND 4 to PND 10, a period of brain development equivalent to the third trimester in human, increased the time spent in the open arms of the elevated plus‐maze in offspring of both sexes at prepubertal period (Breit, Zamudio, & Thomas, ). We here showed that prenatally WIN‐exposed animals of both sexes did not exhibit anxious‐like behaviours in the elevated plus‐maze.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the BAC achieved is the critical factor, particularly since alcohol and THC were not administered simultaneously. Moreover, we have previously reported synergistic effects of alcohol and cannabinoids (both on BAC and offspring behavior) when they are administered via different routes during the neonatal period (Breit et al, 2019b(Breit et al, , 2019c, suggesting that synergistic effects are not reliant on a single route of administration. Thus, although this is the first study to administer polydrug exposure via vapor inhalation during the prenatal period, these factors collectively suggest that consequences of prenatal alcohol, as well as the synergistic effects of alcohol and THC, observed in the current study are not due to the route of administration.…”
Section: **mentioning
confidence: 94%